The AI Revolution in Medical Education: Preparing the Future Physician - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into healthcare is no longer a futuristic concept; it is a present-day reality rapidly reshaping clinical pract...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care